Two new scales in the field of couples and marriage counseling: The inclusion of other in the self scale and Turkish self-change in romantic relationships scale - (:unkn) unknown (E D P SCIENCES, 2018)
This study had two aims. One aim was to adapt the Inclusion of Other in the Self (IOS) Scale into the Turkish cultural context. The second aim was to develop the Turkish Self-Change in Romantic Relationships Scale (TSCRRS) based on the existing Relational Self-Change Scale. The research process for this study consisted of four stages. In the first stage, forward-backward translation of the IOS Scale was performed to determine bilingual equivalence. In the second stage, an item-pool was created to measure self-change in romantic relationships. In the third stage, data were collected to determine the reliability and validity of the TSCRRS (N = 426). In the fourth stage, new data were collected to determine the validity and reliability of the IOS Scale and the TSCRRS (N = 348). All of the participants were in a romantic relationship. The findings revealed that both the TSCRRS and the IOS Scale have good reliability and validity.
Keywords: romantic relationships; self-change; the inclusion of other in the self; scale adaptation; scale development; culture; 2-DIMENSIONAL MODEL; ME